Lactobacillus with probiotic potential from homemade cheese in Azerbijan - Khudaverdi Ganbarov; Saeed Mojarrad khangah (BioImpacts, 2014)
Introduction: Lactobacillus is believed to be beneficial in human health, thus the search for isolation and identification of friendly human bacteria from traditional fermented foods is important in medicine. One of the dairy products, traditional cheese as a highly-consumed dairy product could be a valuable source of these friendly edible germs.Methods: In this research, home-made cheese from Lankaran, Jalil Abad and Salian regions in Azerbaijan was characterized for the presence of Lactobacilli with probiotic potential. The bacterial suspension was enriched and screened for acid and bile resistances. Then, the isolates were subjected to antibiotic resistance and antibacterial effects against convenient pathogenic bacteria. The isolates were identified by 16s rDNA sequencing. Results: The results clearly revealed two probiotics with higher homology to Lactobacillus planetarum and Lactobacillus fermentum.Conclusion: No antibiotic resistance was detected in any of the potentially probiotic lactobacilli isolates in these regions, where people continue to follow a life-style that is largely traditional, with traditional medications.